Treatment of Locking of the Metacarpophalangeal Joint of the Thumb - Harada, Yoshifumi; Inui, Atsuyuki; Mifune, Yutaka; Nishimoto, Hanako; Kokubu, Takeshi; Hiroyuki, Fujioka; Kuroda, Ryosuke (Journal of Hand and Microsurgery, 2019)
Locking of the thumb metacarpophalangeal joint is a relatively rare condition. We report successful treatment in 11 cases of locking of the thumb. Ten patients were diagnosed at an average of 3.2 days (range: 0–21 days) from the injury onset, whereas one patient was diagnosed at 4 months from the injury. Seven of 11 cases underwent successful manual reduction, whereas the other four cases required surgical treatment. Among the surgically treated cases, all cases had a sharp prominent of the radial condyle of the metacarpal head. Therefore, this case series showed 1 chronic case and 4 of 10 cases with a nonround shape of metacarpal heads requiring open reduction.
Keywords: locking of the thumb; metacarpal head; open reduction